2018
DOI: 10.1111/vec.12771
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plasma lactate and core‐peripheral temperature gradient in association with stages of naturally occurring myxomatous mitral valve disease in dogs

Abstract: Objective -To evaluate plasma lactate concentrations and core-peripheral temperature gradients as perfusion parameters in dogs with heart failure caused by myxomatous mitral valve disease (MMVD) and to determine whether the above perfusion parameters are correlated with disease stages. Design -Prospective observational study. Setting -University teaching hospital. Animals -After excluding 129 dogs because of exclusion criteria, 7 dogs with heart failure classified as stage B2 and 10 dogs classified as stage C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
0
6
1
2
Order By: Relevance
“…Body weight and RT both decreased over time as dogs progressed into CHF. The decrease in RT is likely to be a consequence of impaired peripheral perfusion . The decrease in BW may be a consequence of the loss of skeletal muscle mass, but we did not record body condition or muscle condition scores at each visit and therefore cannot be sure of this conclusion.…”
Section: Discussionmentioning
confidence: 96%
“…Body weight and RT both decreased over time as dogs progressed into CHF. The decrease in RT is likely to be a consequence of impaired peripheral perfusion . The decrease in BW may be a consequence of the loss of skeletal muscle mass, but we did not record body condition or muscle condition scores at each visit and therefore cannot be sure of this conclusion.…”
Section: Discussionmentioning
confidence: 96%
“…Increased Spec cPL (Texas A&M University, Gastrointestinal Laboratory) concentrations have been reported in dogs with myxomatous mitral valve disease (MMVD) 85 . In 42 dogs with congestive heart failure (CHF), Spec cPL (Texas A&M University, Gastrointestinal Laboratory) concentrations were correlated with severity of heart failure and given that CHF is associated with occult tissue hypoperfusion, we suspect that this correlation may reflect subclinical secondary pancreatic injury in CHF 85,86 . Alternatively, the increased pancreatic lipase concentrations may be secondary to pancreatic edema in the absence of inflammation, which recently was reported in a pilot study of dogs with portal hypertension 87 .…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 98%
“…The two possible explanations for reducing the ability to perform peripheral vasoconstriction were the age of these animals or the use of the pimobendan vasodilator drug. Feger & Braune (2005) corroborated these data by reporting that the advancing age directly influences sympathetic responsiveness in humans, with a reduction in the physiological temperature gradient in elderly patients (Feger & Braune 2005, Lima et al 2009, Soares et al 2018.…”
Section: Introductionmentioning
confidence: 65%
“…Finally, studies showed that a detailed physical examination assists in identifying changes in peripheral perfusion parameters that faithfully reflect the imminent risk of acute circulatory failure. Soares et al (2018) demonstrated that patients with chronic stage C mitral valve disease had increased lactate values even if stable macro-hemodynamically, but with normalized temperature gradients, while animals in stage B2 had altered center-peripheral deltas. The two possible explanations for reducing the ability to perform peripheral vasoconstriction were the age of these animals or the use of the pimobendan vasodilator drug.…”
Section: Introductionmentioning
confidence: 97%